All‐ceramic restoration of zirconia two‐piece implants – a randomized controlled clinical trial. Issue 4 (6th February 2014) - Payer, Michael; Heschl, Alexander; Koller, Martin; Arnetzl, Gerwin; Lorenzoni, Martin; Jakse, Norbert
Abstract Objectives Aim of this controlled prospective randomized study was to evaluate the outcome of two‐piece zirconia implants compared to titanium implants over a period of up to 24 months. Material and methods A total of 31 implants (16 zirconia/Ziterion vario Z® + 15 titanium/Ziterion vario T®) were inserted primary stable (>30 Ncm) in the maxilla (7) and mandible (24) of 22 patients (13 male, nine female) requiring neither bone nor soft tissue augmentation. After a healing period of 6 months in the maxilla and 4 months in the mandible, ceramic abutments were luted adhesively to the zirconia implants and definitive all‐ceramic restoration was performed with high‐density ceramics. Radiographic bone levels, condition of the peri‐implant mucosa, aesthetic outcome, implant survival and success were recorded for up to 24 months. Results Measurements of mean marginal bone levels 24 months after surgery showed a significant bone loss (P < 0.001) in both groups (Ti: 1.43 (SD ± 0.67) vs. Zir 1.48 (SD ± 1.05). One zirconia implant was lost 8 months after restoration. No further complications were recorded, giving an overall survival and success rate of 93.3% for zirconia and 100% for titanium implants after a period of up to 24 months. Conclusions After 24 months, success rates of the two‐piece ceramic implants showed no significant difference compared to control two‐piece titanium implants. The bonded zirconia implant abutment connection appears to be capable with clinical application over the observed period. However, further control measurements need to confirm the presented data.